Pharmacological Treatment of Secondary Lymphedema - Brown, Stav; Dayan, Joseph H.; Coriddi, Michelle; Campbell, Adana; Kuonqui, Kevin; Shin, Jinyeon; Park, Hyeung Ju; Mehrara, Babak J.; Kataru, Raghu P. (Frontiers in Pharmacology, 2022)
Lymphedema is a chronic disease that results in swelling and decreased function due to abnormal lymphatic fluid clearance and chronic inflammation. In Western countries, lymphedema most commonly develops following an iatrogenic injury to the lymphatic system during cancer treatment. It is estimated that as many as 10 million patients suffer from lymphedema in the United States alone. Current treatments for lymphedema are palliative in nature, relying on compression garments and physical therapy to decrease interstitial fluid accumulation in the affected extremity. However, recent discoveries have increased the hopes of therapeutic interventions that may promote lymphatic regeneration and function. The purpose of this review is to summarize current experimental therapeutic approaches to the treatment of lymphedema.